Relationship Between Level Of Knowledge And Attitudes Towards Waste Management Behavior In Neighbouhood 02, Donohudan Village, Ngemplak District, Boyolali Regency - Fatikhah, Hasna Aghnia; Dwi Astuti (JURNAL KESMAS DAN GIZI (JKG), 2025)
Environmental issues are inevitable. Along with population growth, economic activity, and residential expansion, more waste is generated. The amount of waste produced by the community in Boyolali Regency continues to increase every year. Plastic waste from food packaging is scattered along the roadsides around the Donohudan Hajj Dormitory Complex, Ngemplak, Boyolali. This is due to the high volume of group shopping activities by pilgrimage escorts from various regions. The objective of this study is to investigate the relationship between knowledge and attitudes toward waste management in RW 02, Donohudan Village, Ngemplak Subdistrict, Boyolali District. The research method employed was a cross-sectional survey involving 61 respondents selected through random sampling. Data was collected through a questionnaire and analyzed using the chi-square test. The findings of this study indicate a significant relationship between knowledge and attitudes toward waste management behavior in RW 02, Donohudan Village, Ngemplak Subdistrict, Boyolali District (p-value = 0.000).